Gambaran Sanitasi Lingkungan Kerja dan Tingkat Kepadatan Lalat di Satuan Pelayanan Pemenuhan Gizi Kota Manado Tahun 2026 - Arum Anisa Mokodompit; Paul Artur Tennov Kawatu; Woodford Baren Solaiman Joseph; Vennetia Ryckerens Danes (Universitas Pahlawan Tuanku Tambusai, 2026)
The Free Nutritious Meals (Makan Bergizi Gratis/MBG) Program is a government initiative implemented through Nutrition Fulfillment Service Units (Satuan Pelayanan Pemenuhan Gizi/SPPG) to provide nutritious meals for beneficiaries. Food safety in this program is influenced by work environment sanitation and vector control, particularly flies as potential biological contaminants. This study aimed to describe the work environment sanitation and fly density levels at Nutrition Fulfillment Service Units (SPPG) in Manado City in 2026. A quantitative descriptive study with a cross-sectional approach was conducted involving 13 SPPGs selected through purposive sampling. Data were collected through observations of work environment sanitation based on the Indonesian Ministry of Health Regulation Number 2 of 2023 and fly density measurements using the fly grill method at four observation points, namely the main entrance, portioning and packaging area, reusable meal container (ompreng) washing area, and temporary waste storage (TPS) area. The results showed that all SPPGs (100%) met the required work environment sanitation standards, with sanitation scores ranging from 81.40% to 95.35%, although several building and sanitation facility indicators still did not meet the established requirements. The highest fly density was observed in the temporary waste storage area with an average of 8.4 flies per grill, while the lowest was recorded in the portioning and packaging area with an average of 0. It can be concluded that the work environment sanitation at SPPGs in Manado City generally complied with the required standards; however, improvements in several sanitation aspects and strengthened fly control measures are still necessary to support food safety in the implementation of the MBG Program.